Genital and perianal melanoacanthomas - Shenoy Manjunath; Teerthanath S; Bhagavan K (Wolters Kluwer Medknow Publications, 2007)
Melanoacanthoma is a benign mixed tumor of melanocytes and keratinocytes. It has been regarded as a rare variety of Seborrheic keratosis. A 50-year-old male presented with multiple asymptomatic pigmented growths on the lower abdomen, inner thighs, external genitals and perianal areas. Histopathology revealed features of melanoacanthoma. The case is being reported for unusual sites of occurrence of an uncommon cutaneous tumor.